Adventive insect species of the Sayram-Ugam National Natural Park, Kazakhstan - I. I. Temreshev (Acta Biologica Sibirica, 2017)
We present a list of adventive insect species found in the territory of the Sairam-Ugam National Natural Park in the South of Kazakhstan. We identified 11 species, namely: Acanthocinus griseus (Fabricius, 1793), Callidium violaceum (Linnaeus, 1758), Rhagium inquisitor (Linnaeus, 1758) (Cerambycidae) Acanthoscelides pallidipennis (Motschulsky, 1874) (Chrysomelidae), Sitophilus granarius (Linnaeus, 1758), Sitophilus zeamais Motschulsky, 1855 (Dryophtoridae), Dryocoetes autographus (Ratzeburg, 1837), Hylurgops palliatus (Gyllenhall, 1813), Ips sexdentatus (Boerner, 1776) (Curculionidae); Monomorium pharaonis (Linnaeus, 1758) (Formicidae), Dasineura gleditchiae (Osten Sacken, 1866) (Cecidomyiidae). We also considered the invasion patterns of identified insects into the territory of the national park together with probability of stable self-reproducing population here and possible consequences of invasion.